ARTERIAL HYPERTENSION IN PATIENTS WITH RHEUMATOID ARTHRITIS - N. M. Nikitina; A. P. Rebrov (Рациональная фармакотерапия в кардиологии)
Aim. To study a prevalence and peculiarities arterial hypertension (HT) in patients with rheumatoid arthritis (RA).Patients and methods. 584 patients with RA were involved in the study. RA was diagnosed according to ACR criteria (1987).Results. 58,6% of the patients with RA had HT. It is significantly more often than this in common population. HT prevalence was directly related with RA duration and RA activity.Conclusion. High HT prevalence in patients with RA and fast growth of morbidity at the beginning of RA requires accurate blood pressure control for HT early diagnosis and timely therapy. Taking into account wide usage of non steroid antiinflammatory drugs calcium antagonists or angiotensin II receptor antagonists are more preferable in this group of patients.